Fibroblast growth factor 21 associating with serotonin and dopamine in the cerebrospinal fluid predicts impulsivity in healthy subjects - Jinzhong Xu (BMC, 2021)
Abstract Background Impulsivity is more commonly reported in subjects with mental disorders compared to healthy subjects, suggesting a potential application of impulsivity in predicting impulsivity-related mental disorders. However, no biomarker of impulsivity available so far. This study explored the association between cerebrospinal fluid (CSF) fibroblast growth factor 21 (FGF21), a key hormonal mediator of the stress response, and impulsivity in healthy subjects. Methods A total of 126 healthy persons subjected to surgery of anterior cruciate ligament were recruited in the present study. The impulsiveness of the subjects was evaluated by the Chinese version of the Barratt Impulsiveness Scale (BIS)-11 before surgery. CSF and blood samples of the subjects were collected before spinal anesthesia for surgery. The levels of FGF21, serotonin and dopamine in CSF and the level of FGF21 in blood of the subjects were measured by ELISA using commercial kits. Results Negative correlations were found between BIS-11 total score and either FGF21, serotonin or dopamine in CSF. However, BIS-11 total score was not correlated with FGF21 in blood. In addition, FGF21 was positively correlated with serotonin and dopamine in CSF, respectively. Multivariable linear regression models indicated that the decrease of FGF21 level associating with the decrease of serotonin and dopamine level in CSF contributed to the higher impulsivity. Furthermore, receiver operating characteristic curve (ROC) analysis indicated an important role of CSF FGF21 predicting high impulsivity. Conclusions FGF21, serotonin and dopamine in CSF associate with impulsivity in opposite directions. The decrease of CSF FGF21 is related to higher impulsivity, and indicate that CSF FGF21 may predict impulsivity in healthy subjects.